Xanthogranulomatous Inflammation of the Female Genital Tract: Report of Three Cases - Zhang, Xiang-sheng (Ivyspring International Publisher, 2012)
Purpose and Methods: This is a series of three cases diagnosed with xanthogranulomatous inflammation of the female genital with emphasis on the etiology, clinical-pathologic features and biological behavior. Clinical, pathologic, radiologic and follow up data are reported. Results: The three cases of Xanthogranulomatous inflammation of the female genital tract are the followings: 1) one case affecting the endometrium, 2) one case affecting the fallopian tube, and 3) one case confined to the ovary. The patient's age was 37, 22 and 62 year-old, respectively. Histologic examination revealed extensive infiltration of foamy histiocytes admixed with variable amount of inflammatory cells. The later include plasma cells, lymphocytes, and occasional multinucleated giant cells. Immunohistochemistry showed positive staining for CD68, a histiocytic marker, in foamy histiocytes, CD3, a T cell marker, and CD20, a B cell marker, in the background lymphocytes. The plasma cells were polyclonal with expression of both κ and λ light chains. Conclusion: Xanthogranulomatous inflammation of the female genital tract is an unusual lesion, and clinically forms mass- like lesion in the pelvic cavity that invades the surrounding tissues, which may mimic the tumor clinically and by imaging.